Investigations on the Cross-hole Sonic Logging Test on Bored Piles at Bridge 29 in Section 8 for East Coast Rail Link (ECRL) - Binti Mohd Ajis, Siti Humairah; Karthigesu A/L Nagarajoo; Rus Azlizan Bin Mohd Ali (Progress in Engineering Application and Technology, 2023)
East Coast Rail Link (ECRL) project is a new railway line that cover from Kota Bharu, Kelantan to Port Klang, Selangor with a total length of alignment is 665 km. In this project, the structure is focused on bored pile made by cast-in-situ according to the design depth to conduct quality control of concrete integrity and to check visually as it is embedded in the borehole. Therefore, Cross-hole Sonic Logging (CSL) test that is commonly used for bored pile is studied. Then, the CSL test is conducted on bored pile at Bridge 29 in Section 8 by following the guideline procedure specifically for ECRL project. An analysis is conducted in order to evaluate the integrity of bored piles and identify the depth location of any voids or defect inside the bored pile. The results show there are 3 piles are detected to have anomalies over total five piles even though all the anomalies are considered minor. Piles that consist of various defects have bigger value of grout volume as the gaps or voids need to be fill with concrete. This project’s outcome can be a reference for future research of the CSL test especially by using tomography analysis to evaluate more accurate pile integrity.